COMBINED PALEOMAGNETIC, ISOTOPIC, AND STRATIGRAPHIC EVIDENCE FOR TRUE POLAR WANDER FROM THE NEOPROTEROZOIC AKADEMIKERBREEN GROUP, SVALBARD, NORWAY - Maloof A.C.; Halverson G.P.; Schrag D.P.; Hoffman P.F.; Kirschvink J.L.; Weiss B.P. (My University, 2006)
We present new paleomagnetic data from three Middle Neoproterozoic carbonate units of East Svalbard, Norway. The paleomagnetic record is gleaned from 50 to 650 m of continuous, platformal carbonate sediment, is reproduced at three locations distributed over >100 km on a single craton, and scores a 5-6 (out of 7) on the Van der Voo (1990) reliability scale. Two >50° shifts in paleomagnetic direction are coincident with equally abrupt shifts in δ13C and transient changes in relative sea level. We explore four possible explanations for these coincidental changes: rapid plate tectonic rotation during depositional hiatus, magnetic excursions, nongeocentric axial-dipole fields, and true polar wander. We conclude that the observations are explained most readily by rapid shifts in paleogeography associated with a pair of true polar wander events. Future work in sediments of equivalent age from other basins can test directly the true polar wander hypothesis because this type of event would affect every continent in a predictable manner, depending on the continent's changing position relative to Earth's spin axis. © 2006 Geological Society of America.
Keywords: CARBON CYCLE; NEOPROTEROZOIC; PALEOGEOGRAPHY; PALEOMAGNETISM; POLAR WANDERING; SVALBARD; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская